PENGARUH PELATIHAN PUSH-UP TERHADAP PENINGKATAN KEKUATAN MENARIK DAN MENDORONG OTOT LENGAN - Aryana, Gede (Universitas Pendidikan Ganesha, 2013)
This study aimed to determine the affect of training push-up against increased muscle strength of the arm pull and push. This type of research was a quasi-experiment with research design using